Near-infrared fluorescent imaging for parathyroid identification and/or preservation in surgery for primary hyperparathyroidism - Pannu, Arslan Y.; O’Connor-Manson, Magdalena R.; Wyld, Lynda; Balasubramanian, Saba P. (Frontiers in Endocrinology, 2023)
Near infrared autofluorescence (NIRAF) is a novel intraoperative technology that has shown promising results in the localisation of parathyroid glands (PGs) over the last decade. This study aimed to assess the potential utility of NIRAF in first time surgery for primary hyperparathyroidism (PHPT).An observational study over a period of 3 years in patients who underwent surgery for PHPT was designed. Data on the use of NIRAF and fluorescent patterns in different organs (thyroid and parathyroid) and parathyroid pathology (single versus multi-gland disease) were explored. In addition, cure rates and operating times were compared between the NIRAF and no-NIRAF groups to determine the potential value of NIRAF in this cohort.In 230 patients undergoing first time surgery for PHPT, NIRAF was used in 50 patients. Of these 50 patients, NIRAF was considered to aid parathyroid identification in 9 patients (18%). The overall cure rate at 6 months of follow-up was 96.5% (98% in NIRAF and 96.1% without NIRAF; p=1.0). The median (interquartile range) operating time was longer in the NIRAF arm at 102 minutes (74-120 minutes) compared to the no-NIRAF arm at 75 minutes (75-109 minutes); however, this difference was not statistically significant (p=0.542). Although the median parathyroid to thyroid (P/T) auto-fluorescence (AF) ratio was similar between single gland and multi gland disease (2.5 vs to 2.76; p=1.0), the P/T AF ratio correlated negatively with increasing gland weight (p=0.038).The use of NIRAF resulted in some potential "surgeon-perceived" benefit but did not lead to improvements in cure rates. The negative correlation between fluorescent intensity and gland weight suggests loss of fluorescence with pathology, which needs further investigation. Further studies on larger cohorts of patients, in depth analysis of fluorescence patterns between normal, adenomatous, and hyperplastic glands and evaluation of user experience are needed.